1993
DOI: 10.1128/jb.175.1.117-127.1993
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Tn1546, a Tn3-related transposon conferring glycopeptide resistance by synthesis of depsipeptide peptidoglycan precursors in Enterococcus faecium BM4147

Abstract: Sequence determination of the flanking regions of the vancomycin resistance van

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
476
1
5

Year Published

1996
1996
2014
2014

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 554 publications
(494 citation statements)
references
References 56 publications
12
476
1
5
Order By: Relevance
“…Further investigations showed that these genes are a part of Tn 1546, a 10.8-kb transposon that carries the vanRSHAXYZ genes (Arthur et al, 1993). Recent epidemiological studies of dissemination of VanA-type resistance in enterococci indicated the localization of the vanA gene cluster on 34-or 60-kbp plasmids (Clark et al, 1993;Mato et al, 1996), on conjugative >100-kbp plasmid or on the chromosome of bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…Further investigations showed that these genes are a part of Tn 1546, a 10.8-kb transposon that carries the vanRSHAXYZ genes (Arthur et al, 1993). Recent epidemiological studies of dissemination of VanA-type resistance in enterococci indicated the localization of the vanA gene cluster on 34-or 60-kbp plasmids (Clark et al, 1993;Mato et al, 1996), on conjugative >100-kbp plasmid or on the chromosome of bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…The vanA operon is part of transposon Tn1546, which is often carried by self-transferable plasmids, accounting for its spread (9). Dissemination of VanB-type resistance results from the spread of conjugative transposon Tn1549 (10) located on plasmids or in the chromosome.…”
mentioning
confidence: 99%
“…From 2000 to 2002, 20 clinical isolates of vanA-containing Enterococcus faecium were collected from nine different university hospitals in diverse geographic areas in Korea. Previously characterized VRE strain E. faecium BM4147 served as a control (1). Organisms were identified by conventional biochemical reactions, with the Vitek identification system (bioMérieux, Hazelwood, Mo.…”
Section: Methodsmentioning
confidence: 99%